The effect of organizational culture on deviant behaviors in the workplace - Di Stefano, Giovanni; Scrima, Fabrizio; Parry, Emma (Taylor & Francis, 2017)
This study investigated the impact of organizational culture (OC) on deviant behaviors in the workplace (workplace deviant behaviors: WDB). We tested the hypothesis that different types of OC (according to the Competing Values Framework model) had an impact on WDB, in addition to the effect of Big Five personality traits. Survey research was undertaken with 954 employees of 30 enterprises in the public and private field, using a hierarchical model approach (HLM) to test the effects of four types of OC (Clan; Adhocracy; Market, Hierarchy) on WDB, over and above the effect of Five Personality traits. The HLM results partially supported our hypotheses, showing that the OC had a significant effect on WDB, with the adhocracy and clan cultures characterized by lower levels of WDB. Managerial implications about the importance of managing the OC are discussed.
Keywords: Organizational culture; Workplace deviant behaviors; Disruptive behaviors; Competing Values Framework; Personality traits